2018
DOI: 10.1111/jocn.14143
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses’ perceptions of safe care in overcrowded emergency departments

Abstract: This study indicates that emergency departments should review their procedures to avoid both deviations from normal practice and moral stress among registered nurses. This can contribute to an increased understanding and insight about the challenge of patient safety in an emergency department setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 22 publications
1
46
0
6
Order By: Relevance
“…16 After the earthquakes, RSSAD conditions modified the baseline indicators and might have lead to some undesirable outcomes like an increase in waiting times, and a negative perception of safety and quality of attention in health care providers may be present. 17 Our results are in accordance with some previous studies that have reported significant enhancing in census activity of emergency departments of local general hospitals after a natural disaster had occurred. Aitken et al 18 found a significant increase in emergency consultations after Tropical Cyclone Yasi struck Australia on February 2011.…”
Section: Discussionsupporting
confidence: 93%
“…16 After the earthquakes, RSSAD conditions modified the baseline indicators and might have lead to some undesirable outcomes like an increase in waiting times, and a negative perception of safety and quality of attention in health care providers may be present. 17 Our results are in accordance with some previous studies that have reported significant enhancing in census activity of emergency departments of local general hospitals after a natural disaster had occurred. Aitken et al 18 found a significant increase in emergency consultations after Tropical Cyclone Yasi struck Australia on February 2011.…”
Section: Discussionsupporting
confidence: 93%
“…These situations creates moral distress, as staff willingness to create a good encounter often ends up with more discussions about the bed availability and the amount of time spent at the ED than on a patient–provider relationship level. It is well known that crowded EDs and high workflow make the environment stressful 12,21. As access to inpatient beds decreases, ED crowding increases 2,22, with even more pressure on the staff, who are given responsibility for patients for a longer time than the environment is built for.…”
Section: Discussionmentioning
confidence: 99%
“…High workloads and staff shortages have been identified as common stressors for staff working at ED. Stressful factors, together with extended lengths of stay for patients in overcrowded EDs are described as safety risks and are some of the most comprehensive challenges of modern emergency care (12). A consequence of high workload is staff feeling 'too busy to properly do their job' (13).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is difficult to continually practice and reinforce certain skills, because emergency care staff encounter a wide variety of patient presentations in their daily work (Garside et al, ). Emergency departments require faster and more accurate decision‐making than other hospital departments, due to their complex and dynamic environments and uncontrollable and unpredictable workloads (Eriksson, Gellerstedt, Hillerås, & Craftman, ). Specific programs are needed to train nurses to accurately and promptly assess patients' neurological status in the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency departments require faster and more accurate decisionmaking than other hospital departments, due to their complex and dynamic environments and uncontrollable and unpredictable workloads (Eriksson, Gellerstedt, Hillerås, & Craftman, 2018). Specific programs are needed to train nurses to accurately and promptly assess patients' neurological status in the emergency department.…”
Section: Discussionmentioning
confidence: 99%